1997
DOI: 10.1021/jp970641p
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer and Connectivity in Chloroplasts:  Competition between Trapping and Annihilation in Pulsed Fluorescence Induction Experiments

Abstract: Despite the fact that fluorescence induction is a very complicated process, the technique is used to obtain information regarding connectivity in photosynthetic systems. The models generally used for the analysis are oversimplified, which in some cases has led to questionable interpretations. Here we describe the effects of nonlinear loss processes in (pulsed) induction experiments and how they obscure the features attributed to large-scale connectivity in chloroplasts. We simulate the fluorescence induction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Calculations using the equations derived above show that the mixing of the ground state and the excited state with the higher ͑nonresonant͒ excited states does not have much influence on the ground state one-photon absorption for the homodimer. 22,23 This result is in line with the results obtained for molecular aggregates by taking into account the mixing with the two-exciton states. 30 The effect for the homodimer is presented in Fig.…”
Section: Demonstration Of the Excited State Mixingsupporting
confidence: 90%
See 1 more Smart Citation
“…Calculations using the equations derived above show that the mixing of the ground state and the excited state with the higher ͑nonresonant͒ excited states does not have much influence on the ground state one-photon absorption for the homodimer. 22,23 This result is in line with the results obtained for molecular aggregates by taking into account the mixing with the two-exciton states. 30 The effect for the homodimer is presented in Fig.…”
Section: Demonstration Of the Excited State Mixingsupporting
confidence: 90%
“…Such kind of interactions could appear for the coupled monomers containing more than two energy levels. The difference spectra of the homodimer built-up by Bchl molecules 22,23 and the circular dichroism ͑CD͒ spectrum of the homodimer 24 were already discussed. The general theory of the nonlinear optical response of aggregates is already developed.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the whole aggregate can be viewed as a single supermolecule which is fully characterized by a manifold of various accessible energy levels reflecting single and multiple excitations. 26,27,48,49 The resulting stochastic model describing possible transitions between these energy levels has been successfully used to describe non-linear S-S annihilation in LHCII trimers. 32,33 At a high repetition rate of the excitation laser, the formation of triplet states should also be considered, which requires the extension of the stochastic model of an LHCII supermolecule.…”
Section: Resultsmentioning
confidence: 99%
“…While this agrees with the findings of Hemelrijk and van Gorkom (1992) as well as of Lavergne and Rappaport (1998), it calls for a reevaluation of the data of France et al (1992) and their interpretation. Actually, based on model calculations Valkunas et al (1997) already concluded more than 25 years ago that singlet-triplet annihilation is "a more natural explanation for the observations of France et al (1992) than the two-hit model of Valkunas et al (1991)". This explanation is in line with our findings on the lowering of fluorescence yield by HIQ (see preceding section).…”
Section: Saturation Of St-induced Variable Fluorescence Yieldmentioning
confidence: 99%